Tense Categories and the Polysemous -a in Raji - Dhakal, Dubi Nanda (Nepalese Linguistics, 2022)
This paper compares the tense system in three Raji varieties and explains the semantics of the  polysemous suffix -a in Purbiya Raji. The Raji variety spoken in Kumaun India differs significantly from the rest of the varieties in marking the tenses. It is argued that this suffix has multiple related meanings, such as past tense,  perfective meaning in adverbial clauses, conditional and simultaneous meaning. It can be said that the polysemous suffix -a was related to two broad categories, viz. past and perfective, and conditional including simultaneous meaning. Out of these two, the semantics of the perfective meaning gradually extends to refer to the past time.